2018
DOI: 10.1007/s10803-018-3648-0
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Challenging Behaviors in the Context of Intensive Behavioral Intervention for Children with Autism

Abstract: This study examined the associations between sleep and challenging behaviors for average and night-to-night fluctuations in sleep, in 39 children with autism spectrum disorder (ASD) receiving intensive behavioral intervention (IBI). Child sleep was recorded (via actigraphy) for five nights in conjunction with clinician-reported observations of challenging behaviors. Results indicated that on average, poor sleep was associated with higher rates of repetitive behavior, negative affect, and a composite of overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…Sleep problems are common in autism spectrum disorders, with 40% to 80% of individuals experiencing sleep disturbances that are disruptive to the children or their families. [3][4][5][6][7] The causes of the higher rate of sleep disturbance in children with autism spectrum disorders are still under investigation but they have been found to be associated with biological, psychological, and environmental factors. [8][9][10] There are many reports in the literature of sleep difficulties associated with autism spectrum disorders.…”
mentioning
confidence: 99%
“…Sleep problems are common in autism spectrum disorders, with 40% to 80% of individuals experiencing sleep disturbances that are disruptive to the children or their families. [3][4][5][6][7] The causes of the higher rate of sleep disturbance in children with autism spectrum disorders are still under investigation but they have been found to be associated with biological, psychological, and environmental factors. [8][9][10] There are many reports in the literature of sleep difficulties associated with autism spectrum disorders.…”
mentioning
confidence: 99%
“…The repetitive restricted behavior (RRB) compasses a wide range of symptoms, including repetitive language, movements, and use of objects, adherence to nonfunctional routines and rituals, restricted interests, and sensory seeking behaviors, sensitivities, and sensory aversions [1]. RRB is associated with increased sleep problems, such as bedtime resistance and insomnia [5], as well as short sleep duration [17,23]. Research examining subcategories of repetitive behavior in ASD found repetitive sensory motor (RSM) behavior (repetitive use of objects, complex motor mannerisms, and sensory seeking behaviors) predicted parent-reported sleep problems, even after controlling for anxiety symptoms, whereas insistence on sameness (IS) was not significantly associated with sleep problems [24].…”
Section: Repetitive Restricted Behaviormentioning
confidence: 99%
“…Internalizing behavior, namely, means behavior that is lashing out at the self. Children with ASD and sleep problems are at great risk of exhibiting internalizing behaviors, such as affective problems (e.g., anxiety, depression, anger), self-injurious behavior (any actions that cause or have the potential to cause physical harm or injury to self), social withdrawal problems, inattention [14], and stereotypes (repetitive movements and behavior) [23,24]. Among 193 preschool-aged Japanese children with ASD, the severity of sleep problems, especially insomnia, was significantly correlated with behavioral problems in ASD preschoolers [8].…”
Section: Internalizing Behaviormentioning
confidence: 99%
“…Melatonin is the most studied and utilized choice for children with ASD (Hollway and Aman 2011b;Malow et al 2016). Multiple studies have documented an association between higher rates of repetitive behaviors and the use of medication for sleep (Abel et al 2018;Malow et al 2016).…”
Section: Current Knowledgementioning
confidence: 99%